The effects of a 12-week combined strength and endurance training program on physical performance of patients with type 2 diabetes - Rogon, Isabella; Kasprzak, Zbigniew; Juhl, Carsten; Mensberg, Pernille; Vilsbøll, Tina; Pilaczyńska-Szcześniak, Łucja (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical training is considered an effective means of preventing and treating diseases of affluence such asT2DM. The key benefits of this therapy include improvements in physical performance and in metabolic processes. Aim of Study. The aim of this study was to investigate the impact of a 12-week long supervised combined strength and endurance training program on physical performance of T2DM patients with various complications. Material and Methods. The study was carried out on patients stratified into Groups (levels) 2 and3 according to the criteria from the 2007 Danish program “Forløbsprogram for Type 2 Diabetes” (see Table 1). A total of 83 patients (29 women, 54 men) participated in the study, aged 65.5 ± 10.62 years. The subjects were offered 60 minutes of supervised group exercise, twice a week for 12 weeks. Each session consisted of a 5-min warm-up, 35-min strength exercise, and 10-min aerobic bicycling, with a load between 12 and15 on the Borg Scale. Physical performance was measured using a 30-second sit-to-stand test (STS) and 6-minute-walktest (6MWT). Results. A significant improvement in STS was noted in Group 2 (mean = 1.6 ± 2.39; 95% CI 0.92-2.3) and in Group 3 (mean = 1.46 ± 2.14; 95% CI 0.74-2.17). Statistically significant (p <0.0001) 6MWT results were obtained in Group2 (mean = 46.7 ± 54.08; (95% CI 30-63) and in Group 3(mean = 46.2 ± 79.51; 95% CI 12-79). Participation in training sessions played a paramount role in improving the effectiveness of combined strength and endurance training. Conclusion. Participation in a 12-week exercise program increased physical performance in patients with type 2 diabetes, regardless of their complication status
Keywords: type 2 diabetes; risk stratification; physical function; physical training